Evidence-Based Procedural Dermatology - Alam, Murad (Springer New York, 2012)
In Evidence-Based Procedural Dermatology, Dr. Alam has compiled the subspecialty's latest research findings in a reference for researchers and dermatologists. It covers the spectrum of procedural dermatology, including skin cancer surgery, laser techniques, fillers and neurotoxins, minimally invasive cosmetic surgery, and emerging procedures. Leading experts present and evaluate evidence in each subfield, providing a solid manual for the present, and a guide for research in the future. Features: ·         A numerical system to appraise research findings used throughout the book ·         Question and answer section to reinforce knowledge at the end of  most chapters ·         Serves as a tutorial for those interested in performing clinical research. ·         Holds practical value for dermatologists who are treating or counseling patients.